Education Program Regarding Labor Epidurals Increases Utilization by Hispanic Medicaid Beneficiaries: A Randomized Controlled Trial. (October 2019) - Togioka, Brandon M.; Seligman, Katherine M.; Werntz, Megan K.; Yanez, N. David; Noles, Lorna M.; Treggiari, Miriam M.
Abstract : Background: Hispanic women choose epidural labor analgesia less commonly than non-Hispanic women. This may represent a healthcare disparity related to a language barrier and inadequate opportunities for labor analgesia education. It was hypothesized that a language-concordant, educational program regarding labor epidurals would improve epidural utilization in two independent cohorts of Hispanic and non-Hispanic women. Methods: A randomized controlled trial, blinded to anesthesia, nursing, and obstetric providers, was completed at an academic hospital (February 2015 to February 2017). Two cohorts of Medicaid beneficiaries of Hispanic (English- and/or Spanish-speaking) and non-Hispanic ethnicity were enrolled concurrently. The patients were randomized to routine care alone or routine care and an additional educational program comprised of three components: a video show, corresponding pamphlet, and in-person counseling. The primary endpoint was use of epidural labor analgesia. The secondary endpoint was change in response before and after delivery on common misconceptions based on a 12-point epidural questionnaire. Results: Hispanic women randomized to the intervention group were 33% more likely to choose epidural analgesia compared to the routine care group (40 of 50 [80%] vs . 30 of 50 [60%]; risk ratio, 1.33 [95% CI, 1.02 to 1.74]; P = 0.029). For the non-Hispanic cohort, no difference was detected in epidural use between the intervention and routine care groups (41 of 50 [82%] vs . 42 of 49 [86%]; risk ratio, 0.96 [95% CI, 0.80 to 1.14]; P = 0.62), but the study was underpowered to determine a result of no difference. Patients assigned to the intervention had a greater improvement in epidural understanding compared with routine care, among both Hispanic (2.26 vs . 0.74, respectively; difference in change from baseline, 1.52 [95% CI, 0.77 to 2.27]; P < 0.001) and non-Hispanic (1.36 vs . 0.33, respectively; difference in change from baseline, 1.03 [95% CI, 0.23 to 1.75]; P = 0.005) cohorts. There were no adverse events during the trial. Conclusions: The educational program increased epidural use among Hispanic women. The educational program reduced misconceptions regarding epidural analgesia in both Hispanic and non-Hispanic cohorts. Abstract : A language-concordant, educational program regarding labor epidurals during the first stage of labor, in addition to the routine prenatal education, is feasible and does not cause any negative effect. Such an intervention increases epidural use among Hispanic but not non-Hispanic women. It also reduces misconceptions regarding epidural analgesia in both Hispanic and non-Hispanic women.Supplemental Digital Content is available in the text.